The Democrat, the free thinker, the theorist ofpolitical crime (2013)
The legal thought and the ideas are the result of long reflectionand measured maturingprocesses; ideas presented and defended in forums and texts; but those ideas always occur around social realities that influence that process; the ideas and their analysis are the result of the deductive method. The idea of dealing with the great jurists, was none other than the rescueof their thought, their work and their legacy; which ideology remains valid. Luis Carlos Pérez is one of them, known as “The political crime theorist”, author of a monumental legal work of the Colombian Penal law which is analyzed in other countries.